Gonad pathology, sex hormone modulation and vitellogenin expression in Chrysichthys nigrodigitatus from Lagos and Epe lagoons within the southern-lagoon system, Nigeria - Akangbe, Olusola A.; Chukwuka, Azubuike V.; Imiuwa, Maurice E.; Adeogun, Aina O. (Frontiers in Toxicology, 2024)
Introduction: Estrogenic chemicals in aquatic environments impact fish reproductive health, with vitellogenin protein levels serving as a crucial biomarker for xenoestrogen exposure. Limited knowledge exists on estrogenic effects in tropical environments, prompting an investigation into the influence of environmental estrogens on Chrysichthys nigrodigitatus in Lagos and Epe lagoons. Methods: A total of 195 fish samples underwent analysis for vitellogenin protein, sex hormones (testosterone and 17 β-estradiol), and gonad pathology in effluent-receiving areas of the specified lagoons. Results: Gonadal alterations were observed in male and female fish, including empty seminiferous tubules and distorted ovaries. Intersex occurred in 3.81% of Lagos and 3.33% of Epe. Testosterone levels were generally higher in females and males from both lagoons, while E2 levels were higher in females from both lagoons, with Lagos showing higher levels than Epe. Vtg levels were higher in males than females in Lagos samples but showed no significant difference in Epe samples. Discussion: Contaminant analysis revealed similar trends in metals (Hg, As, Cr) and phthalates (DEHP, DBP, DEP) in both sexes in the Epe population. Multivariate depictions from the PCA showed sex-specific patterns of metal uptake (Cd) in male fishes at the Lagos Lagoon. The positive association between higher pH loadings and metal and DBP levels in sediment at the Lagos lagoon suggests the influence of higher alkalinity in lower bioavailability of contaminants. Conclusion: Endocrine disrupting effects were observed in male and female Chrysichthys nigrodigitatus in Lagos and Epe lagoons populations, with notable differences in hormone and contaminant concentrations between the two lagoon systems. Identification of specific contaminants and their spatial and temporal trends can inform targeted management and remediation efforts to protect and restore these valuable aquatic ecosystems.